Characterizing right-angled vessel in macular telangiectasia type 2 with structural optical coherence tomography - Yoo-Ri Chung (Nature Portfolio, 2021)
Abstract We investigated the structural findings on spectral-domain optical coherence tomography (SD-OCT) related to the presence of right-angled vessels (RAV) in patients with macular telangiectasia (MacTel) type 2 with severity 3 in Korea. A retrospective multicenter cross-sectional study was conducted in six tertiary hospitals in Korea; the study included 116 MacTel type 2 eyes with severity 3. The SD-OCT findings were compared between eyes with RAV on fundus photography or fluorescein angiography and those without RAV. Logistic regression was performed to determine factors associated with the presence of RAV. Fifty eyes presented with RAV and 61 eyes without RAV. More eyes presented with only inner retinal (IR) cavities on SD-OCT among eyes without RAV than among those with RAV (P < 0.001). However, eyes with RAV presented with IR disorganization, outer retinal (OR) cavity, and ellipsoid zone (EZ) disruption more frequently than eyes without RAV did (all P < 0.001). These SD-OCT findings were significantly associated with the presence of RAV. The presence of RAV was closely related to IR disorganization, OR cavities, and EZ disruption on SD-OCT. These findings suggest an advanced phase of MacTel type 2.